Using induction to prove,

1 + 1/4 + 1/6 + 1/64 + ... + 1/(2^n)
= (2^(2n)+1)/2^(2n)

Thanks! (sorry abt the previous question)

No problem at all! Let's use mathematical induction to prove the given statement.

First, we'll start with the base case, which is n = 1.

For n = 1, the left-hand side of the equation is:

1 + 1/4 = 5/4

Now, let's substitute n = 1 into the right-hand side of the equation:

(2^(2n) + 1) / (2^(2n)) = (2^2 + 1) / (2^2) = 5/4

As you can see, the equation holds true for n = 1.

Next, we move on to the inductive step, assuming that the equation holds true for some arbitrary value k, where k >= 1. This is called the induction hypothesis.

So, let's assume that the equation is true for n = k:

1 + 1/4 + 1/6 + 1/64 + ... + 1/(2^k) = (2^(2k) + 1) / 2^(2k)

Now, let's prove that the equation is true for n = k + 1.

We need to show that:

1 + 1/4 + 1/6 + 1/64 + ... + 1/(2^(k+1)) = (2^(2(k+1)) + 1) / 2^(2(k+1))

To do this, we can add 1/(2^(k+1)) to both sides of the equation assumed true for n = k:

1 + 1/4 + 1/6 + 1/64 + ... + 1/(2^k) + 1/(2^(k+1))

Using the assumption that the equation holds true for n = k, we can substitute:

(2^(2k) + 1) / 2^(2k) + 1/(2^(k+1))

Now, let's simplify this expression:

= [(2^(2k) + 1) * 2^(k+1) + 1] / (2^(2k) * 2^(k+1))

= [2^(2k+1) + 2^(k+1) + 2^(k+1) + 1] / (2^(2k) * 2^(k+1))

= [2^(2k+1) + 2^(k+1) + 2^(k+1) + 1] / (2^(2k) * 2^(k+1))

= [2^(2k+1) + 2(2^(k+1)) + 1] / (2^(2k) * 2^(k+1))

= [(2(2^(k+1)) + 1)^2] / (2^(2k) * 2^(k+1))

= [2^(k+1) + 1)^2] / (2^(2k) * 2^(k+1))

= [(2^(k+1) + 1) / 2^(k+1)]^2

= (2^(k+1) + 1) / (2^(k+1))^2

= (2^(k+1) + 1) / 2^(2(k+1))

And that matches the right-hand side of the equation for n = k + 1.

Therefore, by mathematical induction, we have shown that the equation holds true for all positive integers n.